Integrated Alcohol Use Disorder and Liver Disease Management - Blaney, Hanna; Horhat, Adelina; Saleem, Abdulmalik; Winder, Gerald S.; Mellinger, Jessica; Arab, Juan P. (Seminars in Liver Disease, 2025)
Alcohol-associated liver disease (ALD) is a leading cause of liver disease worldwide, caused by hazardous alcohol use. Many patients with ALD also have alcohol use disorder (AUD), a chronic mental health condition characterized by a cluster of behavioral, cognitive, and physiological symptoms that indicate continued alcohol use despite significant alcohol-related problems. Comprehensive care of ALD often requires treatment of AUD, and evidence has demonstrated that treating the latter improves patient outcomes. However, only a minority of patients with AUD/ALD receive treatment. Integrative care models where hepatologists work alongside AUD specialists have been developed. These partnerships have been associated with improved outcomes, including decreased rates of return to alcohol use, decreased healthcare utilization, and even improved mortality. We review the epidemiology, diagnosis, and treatment of AUD and ALD, examples of successful integrated care models, and outcomes. We also discuss knowledge gaps and areas where future research is needed, including the role of integrated care in the peri-transplantation period for ALD, harm reduction approaches, and the need for efforts to support collaboration for integrative care. In conclusion, the dual pathologies of AUD and ALD necessitate multidisciplinary care, and integrated care models have been shown to be both feasible and effective.
Keywords: alcohol-associated liver disease; alcohol use disorder; integrated care